PRÊMIO NOBEL: O CRIADOR, O PRÊMIO E OS LAUREADOS - Maidana, Rosa Lúcia Vieira; Chagas, Lucas Ávila; Silveiro, Sandra Pinho (Clinical and Biomedical Research, 2020)
PRÊMIO NOBEL: O CRIADOR, O PRÊMIO E OS LAUREADOS